Carbon Dioxide Oversolubility in Nanoconfined Liquids for the Synthesis of Cyclic Carbonates. Issue 11 (7th April 2017) - Zakharova, Maria V.; Kleitz, Freddy; Fontaine, Frédéric‐Georges
Abstract: The physical phenomenon of gas oversolubility in nanoconfined liquids was successfully applied for the catalytic cycloaddition of carbon dioxide to epoxides to generate organic cyclic carbonates. Hybrid adsorbents based on MCM‐41 and SBA‐15 mesoporous silica materials were synthesized, and efficient nucleophile deposition on the surface of the support was achieved through a grafting procedure, which allowed for an effective and durable metal‐free catalytic system. Room‐temperature transformation of styrene and hexene oxides to the corresponding organic carbonates at atmospheric pressure of carbon dioxide was explored. Abstract : Solving the problem : The physical phenomenon of gas oversolubility in nanoconfined liquids is applied for the catalytic cycloaddition of carbon dioxide to epoxides to generate cyclic carbonates at room temperature under atmospheric pressure. A hybrid adsorbent based on the MCM‐41 silica material exhibits enhanced catalytic properties and multicycle stability, providing an effective and sustainable catalytic system.